Reflections on elderly autonomy and its meaning for the practice of nursing care - Raquel Spindola Samartini; Viviane Cristina Cândido (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To reflect on autonomy in health care, its perspective on the lives of the elderly, and its meaning for the practice of nursing care. Methods: Theoretical essay on the practice of nursing care to promote autonomy and self-care for the elderly. Results: It is necessary to qualify the practice of nursing care to consider the aging process and maintain the autonomy of the elderly. Three parts emerged: "The autonomy of the elderly and the care plan", "Nursing in the self-care process", and "Challenges to the practice of caring for the elderly in nursing". Final considerations: There is still a deficiency in promoting autonomy for the elderly due to the need for a review of the practice of nursing care, which, considering aging in Brazil, needs to undertake new actions in order to encourage self-care and autonomy in this population.